Model Rekonstruksi Administrasi Publik Inklusif Untuk Pencegahan Konflik Berulang di Poso: Analisis Sistematis Literatur Multidisiplin - Yakin Ngguna (Journal on Education, 2025)
This study aims to reconstruct a public policy model based on inclusive administration to prevent recurring conflicts in post-conflict regions. Using a Systematic Literature Review (SLR) approach guided by the PRISMA framework, this research analyzed fifteen multidisciplinary studies spanning psychology, sociology, education, law, theology, culture, and ecology published between 2008 and 2025. The synthesis reveals five dominant models supporting inclusive governance: psychosocial approaches emphasizing trust-building and threat perception reduction; multicultural and transitional justice education fostering tolerance and empathy; cultural and theological values reinforcing social legitimacy; community-based moderation and dialogue promoting interfaith harmony; and socio-ecological resilience enhancing sustainable peace. The results indicate that inclusive administration provides a comprehensive framework integrating structural, cultural, and psychological dimensions into public policy. The study contributes theoretically by consolidating fragmented empirical evidence into a cohesive conceptual model, methodologically by employing multidisciplinary synthesis, and practically by offering policy guidance for participatory and sustainable post-conflict governance. Inclusive public administration is thus positioned as an effective paradigm for achieving restorative and lasting peace in diverse societies.